The stone fruit industry in the Mediterranean region: agronomic and commercial overview - Bassi D.; Pirazzoli C. (Stone fruit viruses and certification in the Mediterranean countries: problems and prospects, 1998)
The first part of this work deals with agronomic and varietal aspects. Stone fruit trees now diffused throughout the Mediterranean, represent a genetic resource which has differentiated in over twenty centuries of cultivation after introduction from the Near and the Far East. The most widespread cultivars were derived directly from this germplasm or from programmes of genetic improvement set up in other countries. The second part addresses the production and marketing aspects of stone fruits produced in the Mediterranean area. For peach, apricot, plum, cherry and almond, the trend of supply is discussed for the main producing countries and the trade with foreign countries for the period between 1979 and 1997.